Identifikasi Genangan Banjir yang Terjadi di Kecamatan Cikampek, Kabupaten Karawang - Deandra Auliana Izmah; Eka Wardhani; M. Candra Nugraha (Journal of Mechanical Engineering and Mechatronics, 2019)
Cikampek District is one of the sub-districts in the Karawang Regency located in the Southeast part of the Karawang Regency area. Cikampek sub-district is one of the areas that is growing rapidly due to the development of industrial allotment areas and urban settlements. This study aims to determine the flood inundation that must be addressed immediately. The research method was carried out by observation in the field and interviews with related parties. Based on the results of research in the District of Cikampek, there was inundation with an area of 274 Ha, inundation height of 10-40 cm, drainage time of 3 hours / day, and inundation frequency (9 times / year) due to overflow of secondary drainage channel namely Cikaranggelam River. There are three priority areas that the drainage system must immediately address, namely Desa Cikampek Selatan, Dawuan Tengah and Dawuan Barat.